SÍNTESE DE DERIVADOS DO FURFURAL E DA δ-GLUCONOLACTONA COM POTENCIAL ATIVIDADE ANTI-INCRUSTANTE - Mbengue, Abdoulaye (2010)
Currently, there is a great interest in the research substances for potential inhibition of scale, since depositions of sulfates and carbonates are .causing of many damages to the system of production and decrease of the productivity in the oil wells. In this context, the substance synthesis with scale potential activity has led to an intense research to minimize the scale phenomenon. In such a way, this work describes the synthesis of δ-gluconolactona and furfural derivatives. Hydrazone and esters derivatives with probable capacities incrustation inhibitors had been gotten. The synthesized substances had been:2-hydroxyethyl furan-2-carboxylate (47, 67%), 2-(2-hydroxyethoxy)ethyl furan-2-carboxylate (49, 70%), (E)-2-hydroxyethyl 3-(furan-2-yl)acrylate (48, 63%), (E)-2-(-hydroxyethoxy)ethyl3-(furan-2-yl)acrylate(50,56%); 2S,3R,4S,5S-2,3,4,5,6-pentahydroxyhydrazide, (54, 80%); 2S,3R,4S,5S-2,3,4,5,6-pentahydroxyhydrazide,(54a, 79%); (E)-N-benziylidene-2,3,4,5,6-pentahydroxyhexanehydrazide, (55, 83%);(E)-N-(4-hydroxybenziylidene)-2,3,4,5,6-pentahydroxyhexanehydrazide, (57, 72%);(E)-N-(4-nitrobenziylidene)-2,3,4,5,6-pentahydroxyhexanehydrazide, (56, 69%); (E)-N-(furan-2-ylmethylene)-2,3,4,5,6-pentahydroxyhexanehydrazide, (58, 80%);2,3,4,5,6-pentahydroxy-N`-phenylhexanehydrazide, (66, 75%); 3-methyl-1-phenyl-1H-pyrazol-5-ol, (59, 82%;) 5-chloro-3-methyl-1-phenyl-4-formyl-1-H-pyrazol- (60,90%); 5-chloro-3-methyl-1(4-nitro-phenyl)-4-formyl-1-H-pyrazol, (61, 60%). The analytical study on the activity of inhibition of scale was made with the hydrazid (54) and showed 38, 04% of efficiency of Ba2+inhibition.